Identification of PSEN2 mutation p.N141I in Argentine pedigrees with early-onset familial Alzheimer's disease - Muchnik, Carolina (2015)
Presenilin 2 gene (PSEN2) mutations account for <5% of all early-onset familial Alzheimer's disease (EOFAD) cases and only 13 have strong evidence for pathogenicity. We aimed to investigate the presence of PSEN2 mutation p.N141I and characterize the clinical phenotypes in 2 Argentine pedigrees (AR2 and AR3) with clinical symptoms of EOFAD. Detailed clinical assessments and genetic screening for PSEN2 and APOE genes were carried out in 19 individuals of AR2 and AR3 families. The p.N141I mutation was identified in all affected subjects and was associated with prominent early onset, rapidly progressive dementia, neurologic, and behavioral symptoms. AR2 and AR3 families share the same Volga German ancestry as all the families reported presenting this mutation. To our knowledge, this is the first report of PSEN2 mutation p.N141I in Argentina and even more, in South America. Our contribution increases the total number of described families carrying this mutation and help to improve the characterization of clinical phenotype in EOFAD associated to PSEN2 mutations.